USING ARTIFICIAL INTELLIGENCE TOOLS LIKE CHATGPT IN LANGUAGE TEACHING - Komilova Mukhtasar Abdunabi qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Artificial Intelligence (AI) tools, such as ChatGPT, are revolutionizing the field of language teaching by providing innovative methods for personalized and interactive learning. ChatGPT, a language model powered by AI, serves as a versatile virtual assistant capable of enhancing language acquisition through conversational practice, instant feedback, and tailored lesson creation. By simulating realistic dialogues, it helps learners practice communication skills in a low-pressure environment. Additionally, the tool can clarify grammar, suggest vocabulary improvements, and generate engaging language exercises. Teachers benefit from ChatGPT’s ability to assist in lesson planning, answer student queries, and adapt resources to varying proficiency levels. However, effective integration requires critical awareness of its limitations, including occasional inaccuracies and the need for human oversight to ensure cultural and contextual relevance. When thoughtfully utilized, ChatGPT complements traditional teaching methods, fostering autonomous learning and making language education more accessible and engaging.